2018
DOI: 10.3390/toxins10030112
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Cytochrome P450s and the P450 Complement (CYPome) of Fusarium graminearum

Abstract: Cytochrome P450s (CYPs), heme-containing monooxygenases, play important roles in a wide variety of metabolic processes important for development as well as biotic/trophic interactions in most living organisms. Functions of some CYP enzymes are similar across organisms, but some are organism-specific; they are involved in the biosynthesis of structural components, signaling networks, secondary metabolisms, and xenobiotic/drug detoxification. Fungi possess more diverse CYP families than plants, animals, or bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 178 publications
1
66
0
Order By: Relevance
“…This indicates that P450s play a key role in fungal species’ physiology in terms of their primary and secondary metabolism. Fungal P450s’ role in fungal species’ physiology and their biotechnological application has been thoroughly reviewed [ 8 , 9 , 10 , 11 ]. Among all fungal P450 applications, the use of P450s as drug targets against fungal pathogens is well explored [ 12 , 13 ] because of their binding affinity to azole drugs, which are widely used for treating fungal infections [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that P450s play a key role in fungal species’ physiology in terms of their primary and secondary metabolism. Fungal P450s’ role in fungal species’ physiology and their biotechnological application has been thoroughly reviewed [ 8 , 9 , 10 , 11 ]. Among all fungal P450 applications, the use of P450s as drug targets against fungal pathogens is well explored [ 12 , 13 ] because of their binding affinity to azole drugs, which are widely used for treating fungal infections [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coexpression cluster also contains a variety of transporters such as Major Facilitator Superfamily (MFS) transporter that could be used to secrete gliotoxin and other metabolites potentially synthesized by the coexpression cluster. Additionally, the coexpression cluster contains large numbers of cytochrome P450s, which are decorative enzymes essential for secondary metabolite synthesis (42). In addition to the discussed genes, we observed multiple genes coding for hypothetical proteins in the cluster.…”
Section: Figure 1 Coexpression Analysis Of Specialized Metabolic Hubmentioning
confidence: 81%
“…It has been reported that a more divergent cytochrome P450 oxidase could be involved in secondary biosynthesis [56]. Therefore, we searched the genome of F. filiformis for proteins with a P450 conserved domain using the NCBI CDD tool and BLASTp [40].…”
Section: Cytochrome P450s In the F Filiformis Genomementioning
confidence: 99%